2016
DOI: 10.1080/00071668.2016.1219977
|View full text |Cite
|
Sign up to set email alerts
|

Haematological parameters, serum lipid profile, liver function and fatty acid profile of broiler chickens fed on diets supplemented with pomegranate seed oil and linseed oil

Abstract: The objective of the present study was to determine effect of pomegranate seed oil (PSO) and linseed oil (LO) on haematological parameters, serum lipid profile and liver enzymes as well as fatty acids profile of adipose tissue in broilers. Broilers (n = 400) were fed on diets containing graded PSO levels (0.0%, 0.5%, 1.0%, 1.5%) with or without 2% LO. After 6 weeks of feeding, 6 male broilers from each group were slaughtered and abdominal fat, liver and blood samples were collected. Mixtures of pomegranate see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…Different fat sources did not affect the indicators of liver functions (i.e., GPT and GOT) ( Manterys et al., 2016 , Keum et al., 2018 ), which indicates that BSFL oil did not induce toxic or adverse effect on liver functions. As to serum cholesterol, perplexed results were emerged from this study.…”
Section: Discussionmentioning
confidence: 90%
“…Different fat sources did not affect the indicators of liver functions (i.e., GPT and GOT) ( Manterys et al., 2016 , Keum et al., 2018 ), which indicates that BSFL oil did not induce toxic or adverse effect on liver functions. As to serum cholesterol, perplexed results were emerged from this study.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have demonstrated broilers fed diets rich in SFA showed increased fatty acid deposition in chicken than those fed diets rich in PUFA [ 2 , 12 ]. The MO in our study containing 20% palm oil and 15% linseed oil, palm oil is rich in SFAs and is more stable than linseed oil, while a combination of them would increase stability of the fats and maintenance of an appropriate balance between SFAs and PUFAs [ 10 , 30 ]. Our study also found broilers fed MO1 had decreased concentration of C18:1n-9 and C18:3n-3, as well as increased content of C20:5n-3, C22:6n-3, n-6 PUFA, n-3 PUFA, and total PUFA in breast muscle.…”
Section: Discussionmentioning
confidence: 99%
“…α-eleostearic acid ( cis -9, trans -11, trans -13 CLNA) supplementation significantly lowered blood TAG level in diabetic rats [ 95 ]. Pomegranate seed oil supplementation, which is rich in punicic acid ( cis -9, trans -11, cis -13 CLNA), significantly lowered TC in broilers [ 96 ]. Punicic acid ( cis -9, trans -11, cis -13 CLNA) also significantly decreased ApoB100 secretion by human HepG2 cell in vitro [ 97 ].…”
Section: Conjugated Fatty Acids and Cardiometabolic Healthmentioning
confidence: 99%